HUBUNGAN KOMUNIKASI TERAPEUTIK MAHASISWA DENGAN PERSEPSI PASIEN DI IRNA RSUD UMBU RARA MEHA WAINGAPU - MARIA KARERI HARA; YUNETI OCTAVIANUS NYOKO (Poltekkes Kemenkes Kupang, 2016)
Introduction: Poor communication from nurses can make misunderstandings between nurses and patients also patient’s families. A survey at students third level has practice in hospital showed most of they had therapeutic communication not well. The aims of the study is to known correlation of therapeutic communication students level III with patient perception at Inpatient Care Umbu Rara Meha Hospital Waingapu. Methods: Desain of this study is descriptive study with cross sectional design. The sample is 155 patients who have received treatment from students level III. The independent variables are therapeutic communication orientation phase, phase of work, termination phase and the dependent variable is the perception of the patient. Data were collected with interviews using a questionnaire. Data were analyzed by univariate and bivariate with Chi-square. Results: Most of the patient perception showed students level III has poor therapeutic communication (123 people; 79.4%). Results of this study also found has correlations therapeutic communication at orientation phase with patient perception (OR=12.710; 95% CI= 6.023 - 26.821; p-value = 0.001), has correlations therapeutic communication at phase of work with patient perception (OR=4.691; 95% CI=2.160-10.187; p-value = 0.001) and has correlations therapeutic communication at termination phase with patient perception (OR=3.460; 95%CI=1.970-6.077; p-value=0.001). Suggested: For the hospital, expected to improve the guidance clinic by CI. For educational institutions expected to improve the student guidance and practical experience in the laboratory and hospital specially skill therapeutic communicating also improving the quality of learning therapeutic communication.